PENGARUH KOMPETENSI, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA SMP NEGERI 1 PURWODADI GROBOGAN - Pudjiastuti, Enni -; Sriwidodo, Untung - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2011)
ABSTRACT This research is motivated SMP Negeri 1 Purwodadi is the only school in the district RSBI Grobogan, it is necessary competence, work discipline and job satisfaction will affect the performance. The purpose of this research is to find answers to these problems. Teacher population SMP Negeri 1 Purwodadi some 66 people. Samples were taken using the census, the overall retrieval techniques. Data collection through questionnaire validity and reliability. Technical analysis using multiple linear regression with the classical assumption. Conclusion of the study: (1) The hypothesis that there is a significant influence on the performance of teacher competence SMP Negeri 1 Purwodadi proven true., (2) hypothesis which states that there is a significant influence on the performance of teachers' work discipline SMP Negeri 1 Purwodadi not truth, (3) the hypothesis that there is a significant influence on the performance of the teacher job satisfaction SMP Negeri 1 Purwodadi proven true, (4) the hypothesis that job satisfaction has a dominant influence on teacher performance SMP Negeri 1 Purwodadi shown were correct. Keywords: competence, work discipline, job satisfaction, performance.